Wildfires as a Public Health Problem: a Setting for Nursing in Disasters - R Mauricio Barría P (Universidad de Antioquia, 2019)
Climate change and global warming are phenomena that are progressively affecting the planet. Temperature changes have been posing mayor threats for different domains of human society. One of these threats is related to health due extreme temperatures, and natural disasters. Thus, it is constituted as a global threat to biodiversity and the human population, since not only affects ecosystems equilibrium but increasing wildfires as consequence of increased temperaturesand diminished precipitations. Moreover,wildfires have concentrated attention not only because of their ecological and environmental consequences but also for affecting production, economics, and health of people potentially exposed to environmental risks such fire, smoke, and others chemical products released from wood combustion process.   How to cite this article: Barría RM. Wildfires as a Public Health Problem: a Setting for Nursing in Disasters. Invest. Educ. Enferm. 2019;37(3):e01.